Effectiveness of the Merit System in Office Administration within the Sinjai District Government - Erwin Darmawan; Andi Pangerang Moenta; Achmad Ruslan (LEGAL BRIEF, 2023)
This study aims to find out and analyze the extent of the effectiveness of the implementation of the merit system in fulfilling positions within the Sinjai district government and analyze how aspects of the merit system affect the application of the merit system itself. The results of this study show that (1) the effectiveness of the implementation of the merit system has not run optimally judging from the achievement of mapping the potential and competence of employees who are still far between employees who have and have not implemented competencies. Because if it is related to the regulation of the Permenpan RB Number 38 of 2017, it is explained that employees who occupy positions must first hold a competency test to determine the eligibility of the employee to occupy the position. This is also because there are several obstacles faced in the field, namely; the presence of budget constraints; There is still a lack of understanding of civil servants; There is still a lack of interest in civil servants; Inadequate facilities and facilities; There is no Assessor Functional Officer yet. (2) Aspects of the Merit System are very influential in the process of determining an employee in a position, because in determining a person in a promotion, it is necessary to look at a person's competence, performance, and career pattern by referring to the applicable employee rules. An employee has the right to develop competencies and career clarity that supports it.